2018
DOI: 10.2478/bgeo-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to reconstruct selected elements of the original site topography of the Teutonic castles at Unisław and Starogród (Chełmno Land, Northern Poland) based on archaeological and cartographic data

Abstract: The article presents an attempt to reconstruct the original site topographies of 13 th -century Teutonic castles at Unisław and Starogród, which have not been preserved in the surface terrain. The archaeological remains of both castles are located in the west of Chełmno Land, on the edge of a moraine plateau 30 to 50 metres above the floor of the Vistula valley. The reconstruction used a research approach known as Historical GIS (HGIS), which, besides archaeological data, employs digitised historical cartograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The reconstructed plan of the tower house and defensive walls shows that the north-west wing and part of the south-west wing extended beyond the present-day edge of the plateau of the headland (Figure 6A–B). Molewski et al (2018) have demonstrated that subsequent sand and gravel quarrying have caused landslides, which have destroyed parts of the headland slopes.
Figure 6.Attempted reconstruction of the topography of the castle: A) digital elevation model of the present-day surface; B) digital elevation model of the reconstructed surface (figure by P. Molewski).
…”
Section: Resultsmentioning
confidence: 99%
“…The reconstructed plan of the tower house and defensive walls shows that the north-west wing and part of the south-west wing extended beyond the present-day edge of the plateau of the headland (Figure 6A–B). Molewski et al (2018) have demonstrated that subsequent sand and gravel quarrying have caused landslides, which have destroyed parts of the headland slopes.
Figure 6.Attempted reconstruction of the topography of the castle: A) digital elevation model of the present-day surface; B) digital elevation model of the reconstructed surface (figure by P. Molewski).
…”
Section: Resultsmentioning
confidence: 99%
“…The studies conducted have shown that on the southwest edge there are no relics of the high castle in the form of wall foundations or their negatives (Wasik, ). On that side they have suffered destruction as a result of landslide processes (Molewski, Wasik, & Wiewióra, , 21–25). In addition, the southern slope of the quasi‐peninsula on which the castle is located was terraced in Early Modern times.…”
Section: The Site and Its Discoverymentioning
confidence: 99%